Economic and Social Rights Law Incorporation, Justiciability and Principles of Adjudication - Boyle, Katie (Taylor & Francis, 2020)
The book examines the potential models of incorporation (ways of embedding rights into domestic law) for economic and social rights (ESR) at the national and devolved level and the justiciability mechanisms (adjudication by a court) that enable access to effective remedies in court for violations of ESR. In so doing the book develops principles of ESR adjudication (the building blocks of good practice) and categorises justiciability mechanisms for ESR enforcement at both the national and devolved level.